Comparação de técnicas para concentração de índio de telas de LCD e aplicação de eletro-obtenção - Pereira, Estela Bresolin (2015)
Because of the constant introduction of new technologies to market growth of electronic waste generation has gained importance on the world stage, among these residues are cell phones. Deliver useful life increasingly short. Mobile phones are made up of several components, including LCD screens. In these screens there is a mixture of indium oxide (In) and tin (Sn), known as ITO, which 80-90% consists of In and 10-20% by Sn. There are already several studies that show ideal conditions for comminution and leaching of LCD screens, therefore, this study aims to establish an effective method for concentrating In present in aqueous solution coming from the acid leaching processes and thus regain In the form metal. Tests were conducted electrodialysis (ED), using synthetic solution In2(SO4)3 in order to work with a more environmentally acceptable method. Thus, initially tested for different current densities in a time of 120 minutes, monitoring pH and conductivity and varying the concentration of In every 30 minutes. The In concentration was determined by atomic absorption (AAS). The optimal current density was 0.96 mA/cm2, where was obtained 62.77% current efficiency. After setting the optimal current density applied in the same test of 131 hours, which resulted in a concentration of 521 mg/L In. Despite the use of electrodialysis have been able to concentrate the solution, the value of 521 mg/L is still not enough to recover In for electrowinning. Thus, we apply the solvent extraction method. Was used as DEHPA extractant diluted in commercial kerosene and evaluated the best contact time between the aqueous phase (A) and organic (O), pH, ratio A:O, better DEHPA concentration in the organic phase. For stripping evaluated the best molar concentration of HCl, relative A:O and contact time between phases. The best conditions laid down have been applied in real solution In, obtained leaching LCD screens, with concentration 32.44 mg/L. The best conditions are obtained in the extraction ratio A:O of 40:1, in 20 minutes, at pH 0,5 e obtained a 96,67% efficiency applied after the stripping in the loaded organic solution with In, with respect to 1:10 with concentration of HCl 4M in 10 minutes, resulting in a efficiency of 61,10% and concentration of 7,712 g/L In. Also performed were tests electrowinning (EO) evaluated three different current densities, and 150 A/m² was obtained a 50.71% efficiency at a concentration of 7 g/L. Therefore, two further phases in In recovery process were developed in recovering In its metallic form giving opportunity for new applications, reducing the consumption of natural resources.